The involvement of Krüppel-like factors in cardiovascular diseases - Santoyo Suarez, Michelle Giovanna; Mares Montemayor, Jimena D.; Padilla Rivas, Gerardo Raymundo; Delgado Gallegos, Juan Luis; Quiroz Reyes, Adriana Guadalupe; Roacho Pérez, Jorge A.; Benitez Chao, Diego Francisco; Garza Ocañas, Lourdes; Arévalo Martínez, Gilberto; Garza Treviño, Elsa Nancy; Islas Cisneros, Jose Francisco (Multidisciplinary Digital Publishing Institute, 2023)
Krüppel-like factors (KLFs) are a set of DNA-binding proteins belonging to a family of zinc-finger transcription factors, which have been associated with many biological processes related to the activation or repression of genes, inducing cell growth, differentiation, and death, and the development and maintenance of tissues. In response to metabolic alterations caused by disease and stress, the heart will undergo cardiac remodeling, leading to cardiovascular diseases (CVDs). KLFs are among the transcriptional factors that take control of many physiological and, in this case, pathophysiological processes of CVD. KLFs seem to be associated with congenital heart disease linked syndromes, malformations because of autosomal diseases, mutations that relate to protein instability, and/or loss of functions such as atheroprotective activities. Ischemic damage also relates to KLF dysregulation because of the differentiation of cardiac myofibroblasts or a modified fatty acid oxidation related to the formation of a dilated cardiomyopathy, myocardial infarctions, left ventricular hypertrophy, and diabetic cardiomyopathies. In this review, we describe the importance of KLFs in cardiovascular diseases such as atherosclerosis, myocardial infarction, left ventricle hypertrophy, stroke, diabetic cardiomyopathy, and congenital heart diseases. We further discuss microRNAs that have been involved in certain regulatory loops of KLFs as they may act as critical in CVDs.